151 Overdiagnosis and medical excess in the public eye. (8th June 2022) - Agarwal, Arnav; Hamilton, Keltie; Cassels, Alan; Pellerin, Renee
Abstract : Proposed panelists: Alan Cassels, Renee Pellerin; individuals with lived experience of overdiagnosis (ongoing process to identify individuals via patient advocacy group). Moderators: Arnav Agarwal, Keltie Hamilton. Description: This will be a public-facing panel associated with a formal viewing of the documentary film 'Medicating Normal'. The panel event will focus on: Introduction of concepts related to overdiagnosis and related harm. Contextualizing the documentary film with a focus on profit-drive medicine, other drivers of overdiagnosis, and downstream consequences of medical excess. How individuals, systems and the media reporting may contribute to overdiagnosis and medical excess. Strategies to prevent overdiagnosis at individual and system levels. Challenges regarding evaluating and reporting of overdiagnosis in the media, and how to address them.